Heat transfer characteristics in a non-Newtonian (Williamson) hybrid nanofluid with Hall and convective boundary effects - Alharbi Latifah Falah; Saadeh Rania; Ishak Anuar; Khan Umair; Hussain Syed Modassir; Madhukesh Javali Kotresh; Yılmaz Yalçın; Zaib Aurang (High Temperature Materials and Processes)
Heat transfer (HT) technology is rapidly increasing due to the petition for well-organized heating systems and cooling systems in the requisite posited by chemical, automotive, and aerospace industries. Thus, the present investigation examines mixed convective or buoyancy flow induced by the Williamson fluid closer to the stagnation point worsened by hybrid nanoparticles (alumina [Al2O3] and copper [Cu]) through a flat upright plate by the influence of the Hall effect. The water-based Al2O3 and copper Cu nanoparticles acknowledging convectively-heated as suitable in the industry or engineering are inspected. The dominant equations are non-dimensionalized using the appropriate similarity parameters, and subsequently, using the bvp4c, these are solved numerically. We thoroughly investigate the effects of numerous pertinent parameters on the transverse velocity, the axial velocity, drag force, temperature, and HT. Two dissimilar outputs are perceived in the circumstance of opposing flow, compared to simply one in the assisting flow. The solutions also showed that the thermal boundary layer length increases and the velocity thickness of the boundary layer decreases as a result of the nanofluid. The higher Weissenberg number causes the gradients for the stable result branch to increase, whereas the gradients for the lower result branch drop. The Lorentz force impact can also be utilized to modify the flow and physical characteristics of HT. In addition, the friction factor in the transverse axis enlarges with the magnetic number for both branches.